First line antiepileptics and their hidden risks - a unique case report on diffuse calvarial thickening and twisted tongue linked to the use of phenytoin and sodium valproate - Sankavi Kaarthic; Selvakumar CJ (Asia Pacific Journal of Medical Toxicology)
Introduction: Phenytoin and sodium valproate are widely used antiepileptics with well documented side effects profile. However diffuse calvarial thickening and lingual dystonia with the use of phenytoin and sodium valproate respectively is extremely rare. This case underscores the importance of recognizing rare side effects in patients on long term anticonvulsant therapy.Case presentation: We present two cases of seizure disorder patients who were on first line antiepileptics phenytoin and sodium valproate developed uncommon side effects of diffuse calvarial thickening and lingual dystonia respectively during their follow up. CASE 1: 15 year old boy a case of refractory epilepsy with global developmental delay who was on multiple antiepileptics including phenytoin was admitted with breakthrough seizures. Patient had gum hypertrophy and serum phenytoin level was elevated and CT brain showed diffuse calvarial thickening, the offending drug was stopped. CASE 2: 45 year old female a case of idiopathic generalised epilepsy was started on sodium valproate for seizure control and she developed lingual dystonia during follow up. Having ruled out the secondary causes of dystonia the possible temporal association between the use of sodium valproate and lingual dystonia. Patient improved after stopping the use of sodium valproate.Discussion: This case report highlights two rare adverse effects associated with commonly used anticonvulsants emphasizing the need for heightened clinical vigilance.Early identification is essential for better clinical outcome.Conclusion: Long term use of phenytoin and sodium valproate can lead to rare but significant adverse effects such as calvarial thickening and lingual dystonia.